2021
DOI: 10.1155/2021/9943289
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Spark‐Based Applications with MPI and OpenACC

Abstract: The amount of data produced in scientific and commercial fields is growing dramatically. Correspondingly, big data technologies, such as Hadoop and Spark, have emerged to tackle the challenges of collecting, processing, and storing such large-scale data. Unfortunately, big data applications usually have performance issues and do not fully exploit a hardware infrastructure. One reason is that applications are developed using high-level programming languages that do not provide low-level system control in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Data Analytics: After collecting the data from various sources and converting the format in the prescribed analytics part, the analysis pipeline takes responsibility for further processing of the data. This data is preprocessed with various techniques like scaling, cleaning, and balancing the information in the prescribed format [ 52 ]. The next stage of the data analysis pipeline makes the information passed through the machine learning algorithms, which will be responsible for decision-making.…”
Section: Proposed Systemmentioning
confidence: 99%
“…Data Analytics: After collecting the data from various sources and converting the format in the prescribed analytics part, the analysis pipeline takes responsibility for further processing of the data. This data is preprocessed with various techniques like scaling, cleaning, and balancing the information in the prescribed format [ 52 ]. The next stage of the data analysis pipeline makes the information passed through the machine learning algorithms, which will be responsible for decision-making.…”
Section: Proposed Systemmentioning
confidence: 99%
“…As a result of its widespread use, it significantly contributes to the acceleration of computing. It has been implemented in several research in combination with OpenMP [8][9][10] and OpenACC [5,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies [1,5,[8][9][10][11][12] have shown the possible benefits of integrating more than one programming model through memory exploitation and accelerator utilization. This may increase throughput and improve performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation